Setting condition of downstream surge tank of hydropower station with sloping ceiling tailrace tunnel. (May 2020) - Guo, Wencheng; Zhu, Daoyi
Highlights: A third order nonlinear state equation of HTGS with SCTT is established. Stability of HTGS with SCTT is analyzed based on Lyapunov's first method. SCDST based on stability of HTGS with SCTT is derived. Characteristics of SCDST based on stability of HTGS with SCTT are analyzed. Difference and relation between two SCDSTs are revealed. Abstract: This paper aims to study the setting condition of downstream surge tank (SCDST) of hydropower station with sloping ceiling tailrace tunnel (SCTT). Firstly, the mathematical model of hydro-turbine governing system (HTGS) with SCTT is established and a third order nonlinear state equation is obtained. Then, the stability of HTGS with SCTT is analyzed based on Lyapunov's first method. SCDST based on stability of HTGS with SCTT is derived based on the stability criterion. Finally, the characteristics and influence of SCDST based on stability of HTGS with SCTT are analyzed. The difference and relation between SCDST based on stability of HTGS with SCTT and SCDST based on stability of HTGS with pressurized tailrace tunnel (PTT) are revealed by using comparative analysis. The results indicate that the complete SCDST based on stability of HTGS with SCTT is composed of several inequalities. One of the inequalities is the dominant inequality and determines the stable domain of HTGS and the allowable value of flow inertia. The flow inertia of penstock corresponding to the endpoint of inequality interval is the allowable value of flow inertia that the downstream surge tank is not necessary to set. The section shape of SCTT almost has no effect on the SCDST. From the view of SCDST for hydropower station with SCTT, it is reasonable that the slope of SCTT takes small value. The allowable value of flow inertia of penstock for hydropower station with SCTT is greater than that for hydropower station with PTT.